Kaposi's sarcoma-associated herpesvirus promotes mesenchymal-to-endothelial transition by resolving the bivalent chromatin of PROX1 gene. - Yao Ding (Public Library of Science (PLoS), 2021)
Increasing evidence suggests that Kaposi's sarcoma (KS) arises from Kaposi's sarcoma-associated herpesvirus (KSHV)-infected mesenchymal stem cells (MSCs) through mesenchymal-to-endothelial transition (MEndT). KSHV infection promotes MSC differentiation of endothelial lineage and acquisition of tumorigeneic phenotypes. To understand how KSHV induces MEndT and transforms MSCs to KS cells, we investigated the mechanism underlying KSHV-mediated MSC endothelial lineage differentiation. Like embryonic stem cells, MSC differentiation and fate determination are under epigenetic control. Prospero homeobox 1 (PROX1) is a master regulator that controls lymphatic vessel development and endothelial differentiation. We found that the PROX1 gene in MSCs harbors a distinctive bivalent epigenetic signature consisting of both active marker H3K4me3 and repressive marker H3K27me3, which poises expression of the genes, allowing timely activation upon differentiation signals or environmental stimuli. KSHV infection effectively resolves the bivalent chromatin by decreasing H3K27me3 and increasing H3K4me3 to activate the PROX1 gene. vIL-6 signaling leads to the recruitment of MLL2 and SET1 complexes to the PROX1 promoter to increase H3K4me3, and the vGPCR-VEGF-A axis is responsible for removing PRC2 from the promoter to reduce H3K27me3. Therefore, through a dual signaling process, KSHV activates PROX1 gene expression and initiates MEndT, which renders MSC tumorigenic features including angiogenesis, invasion and migration.